The Effectiveness of Lactobacillus rhamnosus Administration on the Growth of Klebsiella pneumoniae in Mice (Mus musculus) - Ahmad, Izhar Fitrah; Wiriansya, Edward Pandu; Anggita, Dwi; Basri, Rezky Pratiwi Lambang; Sodiqah, Yani; Nurmadilla, Nesyana (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Klebsiella pneumoniae is a bacterium from the Enterobacteriaceae family and is considered one of the most dangerous pathogens. Antibiotics are crucial for treating acute bacterial infections. Using probiotics has become one of the supportive and curative efforts in managing the growth of K. pneumoniae. One probiotic derived from microorganisms is Lactobacillus rhamnosus. This study aimed to determine the effectiveness of L. rhamnosus on the growth of K. pneumoniae in mice (Mus musculus). Methods: This was an experimental post-test study. The study population consisted of mice aged 3 to 4 months, weighing 20 to 40 grams, determined using Federer’s formula. Mice were given standard feed and sterile distilled water. A total of 30 mice were tested and divided into five treatment groups. The distribution colony count test was used for evaluation. Results: Among the five groups studied, probiotic intervention in the group receiving a combination of L. rhamnosus and the antibiotic ceftriaxone showed effective results (p<0.05), as did the group given only the probiotic L. rhamnosus (p<0.05). In contrast, the other groups did not show effective results (p>0.05). Conclusion: The administration of L. rhamnosus is effective as a supportive and curative treatment, but it is not effective as a preventive measure against the growth of K. pneumoniae in mice.